Edited eukaryotic translation initiation factors confer resistance against maize lethal necrosis - Wen, Zhengyu; Lu, Fengzhong; Jung, Mark; Humbert, Sabrina; Marshall, Lisa; Hastings, Craig; Wu, Emily; Jones, Todd; Pacheco, Mario; Martinez, Ivan; Mahabaleswara, Suresh L.; Beyene, Yoseph; et al. (Wiley, 2024)
Maize lethal necrosis (MLN), which is caused by maize chlorotic mottle virus along with a potyvirus, has threatened the food security of smallholders in sub-Saharan Africa. Mutations in eukaryotic translation initiation factors (eIFs), which also facilitate virus genome translation, are known to confer variable resistance against viruses. Following phylogenetic analysis, we selected two eIF4E proteins from maize as the most likely candidates to facilitate MLN infection. A knockout (KO) of each of the corresponding genes in elite but MLN-susceptible maize lines conferred only partial protection. Our inability to knockout both the genes together suggested that at least one was required for survival. When we edited (ED) the eIF4E genes in Mini Maize, however, the plants with the eif4e1-KO became highly resistant, whereas those with the eif4e2-KO remained susceptible. Neither of the causal viruses could be detected in the MLN-inoculated eif4e1-KO plants. The eIF4E2 cDNA in Mini Maize lacked the entire 4th exon, causing a 22-amino acid in-frame deletion, which shortened the protein to 198 amino acids. When we introduced mutations in the 4th exon of the eIF4E2 gene in two elite, MLN-susceptible lines pre-edited for an eif4e1-KO, we obtained as strong resistance against MLN as in eif4e1-KO Mini Maize. The MLN-inoculated lines with eif4e1-KO/eIF4E2-exon-4ED performed as well as the uninoculated wild-type lines. We demonstrate that the C-terminal 38 amino acids of eIF4E2 are dispensable for normal plant growth but are required for the multiplication of MLN viruses. Our discovery has wide applications across plant species for developing virus-resistant varieties.